Density, porosity, and structure of dried cell walls isolated from Bacillus megaterium and Saccharomyces cerevisiae. - Scherrer, R (1977)
Helium displacement and nitrogen adsorption techniques were used to determine the density and porosity, respectively, of freeze-dried cell walls isolated from Bacillus megaterium KM and Saccharomyces cerevisiae. The densities were 1.302 and 1.180 g/cm3, respectively, suggesting noncrystalline solids. The porosities were extremely small, indicating that the cell walls had collapsed and become essentially impervious upon lyophilization.